The Effectiveness of the "I Can Brush My Teeth" Movement and Song Program in Improving Tooth Brushing Knowledge in Children Aged 4-6 - Nila Alya Maulidina; Farida Kurniawati (Eduvest - Journal of Universal Studies, 2024)
Children with good dental health can experience optimal physical, mental and social development, but in reality 9 out of 10 Indonesian children experience dental caries. This study aims to determine the effectiveness of the "I Can Brush My Teeth" singing and dancing program to increase 4 – 6 years old children’s toothbruhing knowledge. This research uses quantitative research method with a within-subjects quasi experimental pre-post design to measure the effectiveness of intervention using movement and song methods delivered through music video clips as a medium for learning children's knowledge regarding the frequency, duration, schedule and benefits of good toothbrushing, as well as providing children with an understanding of the importance of parental involvement. Post test results showed a significant increase in the average children's knowledge score using the non-parametric Wilcoxon Signed Rank Test comparison technique with a P value of 0.002 with a significance limit of <0.05. One week after post-test1 another post-test was done (post-test 2), and the increase of toothbrushing knowledge persists significantly with a P value of 1.000 with a significance limit of <0.05. Based on the results of the data analysis above, it can be concluded that "I Can Brush My Teeth" singing and dancing program is considered effective in increasing the knowledge of children aged 4 - 6 years about good tooth brushing. Further research evaluating the effect of parental involvement using singing and dancing programs on the level of knowledge about good toothbrushing behavior in children aged 4 - 6 years is considered necessary.